Antimicrobial resistance profile of Staphylococcus aureus isolates isolated from ear discharges of patients at University of Hawassa comprehensive specialized hospital - Serawit Deyno; Alemayehu Toma; Mesfin Worku; Muluken Bekele (BMC, 2017)
Abstract Background Drug-resistant microorganism are a growing global danger. Strains of S. aureus have developed resistance to many commonly used antimicrobials due to indiscriminate use of antimicrobials, and treatment becoming a challenge. Studies assessing pattern and determinants of S. aureus resistance in ear infection in Ethiopia are very scarce. This study presents overview of pattern and determinants S. aureus resistance from samples of ear discharge in Ethiopia. Method A prospective cross-sectional study was conducted on patients who visit ENT clinic of University of Hawassa comprehensive specialized hospital from February 1, 2016 to November 1, 2016. 117 specimens were collected with sterile applicator cotton swab from 117 patients with ear discharge visiting the clinic. Data was fed and then edited, cleared, entered and analyzed using SPSS version 20. Result The prevalence of S.aureus infection was 28.2%. S. aureus isolates revealed up to 97.0% level of resistance pattern to the antimicrobials tested. In the determination of the susceptibility of S. aureus on nine selected antibiotics by disk diffusion technique, 97.0% of the isolates were resistant to cloxacilin and 74.2% showed resistance to vancomycin. The overall rate of MDR was 100%, all of the isolates were found to be resistant to more than two tested antimicrobials. Conclusion S. aureus has gotten frighteningly resistant to many of common antimicrobials. Resistance rate to vancomyin is terrifyingly high. It urges us to take measures to delay resistance. Emergence of resistance highlights the value of prudent prescribing of antimicrobials and avoiding their irrational use. Further researches focusing on identifying dynamics promoting resistance, identifying high risk strains and molecular basis of resistance are required.